Effectiveness of Monetary Policy Transmission Mechanism in Indonesia - M. N, Ripdian Nisa; Hayati, Banatul; A. G, Edy Yusuf (Universitas Negeri Semarang, 2018)
This research aimed to analyse monetary mechanism effectivity to manage inflation in Indonesia through interest rate channel, credit channel, and expectation inflation channel. The research used Vector Error Correction Model (VECM) to analyze effectiveness of monetary policy transmission mechanism in Indonesia. The most effective channel was measured by result of Impulse Response Function and Variance Decomposition. They are: (1). The fastest time lag needed since the shock of monetary instruments (rSBI) until the realization of final target of monetary policy (inflation). (2). How strong the variables in each channel response the shock of SBI interest rate and other variable. The data used in this research is quarterly time series dara from 2005Q1 until 2016Q4. The results of this research show that the most effective channel in managing inflation during 2005Q1 until 2016Q4 is inflation expectation channel.